2003
DOI: 10.1002/cjoc.20030210205
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic Simulation of Aggregates in Surfactant/Oil/Water Systems

Abstract: The aggregates in sodium dedecylsufphate (SDS)/dimethylbe& water system have been investigated using dissipative @des dynamic (DPD) simulation method. Thrwgh analyzing threedimen-One is the phase separabion, which is clearly observed by water density and the aggregates in the simulated cell; another is the water morphology it~ reverse rnide, which can be found through the isodensity slice of water including bound water, trapped water and bulky water; the third is about the water/oil interface, i . c. , ionic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Since this is an open access software, we do not see the need to repeat the related details that are already available publicly [58][59][60][61][62][63] . Nevertheless, we found it necessary to provide a few details that are relevant to this work, where dodecane was used as the organic phase, with dodecanoic acid (100 ppm), Brij-35 (100 ppm) and their mixture (50 ppm:50 ppm) as surfactants, and 0.6 M sodium chloride in water as the aqueous phase.…”
Section: Capillary Hydrodynamic Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this is an open access software, we do not see the need to repeat the related details that are already available publicly [58][59][60][61][62][63] . Nevertheless, we found it necessary to provide a few details that are relevant to this work, where dodecane was used as the organic phase, with dodecanoic acid (100 ppm), Brij-35 (100 ppm) and their mixture (50 ppm:50 ppm) as surfactants, and 0.6 M sodium chloride in water as the aqueous phase.…”
Section: Capillary Hydrodynamic Fractionationmentioning
confidence: 99%
“…Let us now explain how we carried out the DPD-MD simulations. To begin with, a coarse grained DPD simulation was carried out for the surfactant molecules in the organic and water phases individually [59][60][61] . In order to carry out these simulations, all the particles were placed at random positions within the rectangular box of 100x100x100 nm 3 and using a grant size as 1 nm 3 .…”
Section: Capillary Hydrodynamic Fractionationmentioning
confidence: 99%
“…There are several simulations that have studied the formation of RMs, as well as their morphology and structural properties, using molecular dynamics 8,9 and mesoscopic-scale simulations. [10][11][12] S. Salaniwal and co-workers 13 were the first group to study the formation of RMs in a supercritical nonpolar solvent. They found that reverse micellization in supercritical carbon dioxide occurs faster than that for micelles in liquid solvents.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 DPD is a coarse-grained simulation technique that allows researchers to achieve longer time and larger length scales, in some cases approaching experimentallyrelevant conditions. 42,43 DPD has been extensively used for studying soft materials, such as copolymers, [43][44][45] nanoparticles, [46][47][48] surfactants, [49][50][51][52][53] and liquid crystals. 25,54,55 The results of these simulations are in general consistent with experiments, and sometimes explain phenomena that are hard to observe with experimental techniques alone.…”
Section: Introductionmentioning
confidence: 99%